Perception of busking regulation by street theatre entrepreneurs - Curtis, Robin; Andera, Michal, 1984-; Bonnici, Michael Anthony; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis analyses entrepreneurial activities in a niche section of the creative industries, namely street theatre. It sets out to address the challenges faced in entering the market, the complex set of regulations that affect the productivity of street performers and lays out a classification model for understanding the industry. Using a set of extensive qualitative surveys of key members in the field, the industry is analysed on a global scale. Combining knowledge from various articles, journals, newspapers, interviews and other sources, a cohesive picture of the art form is presented, and the on-the-ground functioning of the industry is understood. The regulatory effects on street performing are dissected and real-world functional governmental busking schemes are presented to showcase different approaches to managing a thriving street theatre scene. Finally, an extensive, first-of-its-kind, worldwide quantitative survey is conducted to analyse the perception of busking regulation by street theatre entrepreneurs themselves.
Vedoucí práce: Michal Andera
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses